Remote control system - Izarina, Hipeny (Universiti Malaysia Sarawak (UNIMAS), 2000)
The remote control or radio-controlled system is a common device used in everyday life. Besides being a simple utility, it is nowadays a necessity. This writing gives an overview of the remote control system. It further explains in detail the components used in the construction of a remote control, and its operation. The hardware part, which is the remote control itself including the transmitter, receiver and interfaces constructed, would be produced to further understand the system.